2022
DOI: 10.3390/jcm11237128
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function in Subjects Conceived through Assisted Reproductive Technologies

Abstract: Subjects conceived through assisted reproductive technologies (ART) potentially suffer from impaired left ventricular (LV) function due to premature vascular aging. This study aimed to evaluate whether subtle differences in LV diastolic function can be observed echocardiographically between young ART subjects and their spontaneously conceived peers. The echocardiographic assessment included the measurement of LV dimensions, mitral inflow velocities, and myocardial velocity at early diastole (E’, cm/s) at the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
1
1
0
1
Order By: Relevance
“…A recent study found lower LV systolic function in ART subjects compared to spontaneously conceived peers. However, after adjusting for birth weight percentiles and gestational age, M-mode-assessed LV systolic function showed no significant differences between the groups (21). Similarly, lower diastolic function in ART subjects was found in another study after adjusting for age, birth weight percentile, and gestational age (81), and there were no significant differences in LV diastolic function between the two groups.…”
Section: Cardiovascular Alterations Induced By Assisted Reproductive ...mentioning
confidence: 75%
“…A recent study found lower LV systolic function in ART subjects compared to spontaneously conceived peers. However, after adjusting for birth weight percentiles and gestational age, M-mode-assessed LV systolic function showed no significant differences between the groups (21). Similarly, lower diastolic function in ART subjects was found in another study after adjusting for age, birth weight percentile, and gestational age (81), and there were no significant differences in LV diastolic function between the two groups.…”
Section: Cardiovascular Alterations Induced By Assisted Reproductive ...mentioning
confidence: 75%
“…As this pilot study was part of the Munich heARTerY-study (assisted reproductive technologies and their effects on heart and arterial function in youth), inclusion and exclusion criteria focused primarily on the pediatric cohort [12][13][14][15][16]. To assess whether parents with history of ART displayed an increased cardiovascular morbidity, no exclusion criteria were applied for the parental cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Для оцінки функції лівого шлуночка використовували парастернальні проекції по довгій і короткій осі та апікальні 2 -і 4-камерні проекції. Залежно від якості зображень ФВ ЛШ розраховували двовимірним методом (тобто Simpson) або методом M-mode (тобто Teichholtz) [23].…”
Section: навантажувальний тестunclassified